Attitude Scale Approach to Measuring Religious Attitudes in Islamic Religious Education Learning - Mahfud Heru Fatoni; Baron Santoso; Hamid Syarifuddin; Achmad Rasyid Ridha (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Measuring religious attitudes in Islamic Religious Education has its own challenges. To understand the level of students' attitudes towards religious material, appropriate and relevant instruments are needed. Purpose. This study aims to identify and evaluate the types of attitude scales used in Islamic religious education and to provide recommendations for their use in Islamic religious education. Method. This article was compiled using a library research method. In data collection, sorting and selection were carried out on the concepts and definitions found. The analysis method used involves two main approaches, namely deductive and inductive. The deductive approach is used by drawing conclusions from general facts that have been known to produce more specific conclusions. The inductive approach is applied to draw conclusions from concrete phenomena or situations towards a more abstract understanding. Results. The results of the study of the types of attitude scales are the Likert scale, Guttman scale, semantic differential, and rating scale. Conclusion. The use of various types of measurement scales provides an effective tool for measuring students' attitudes, perceptions, and understanding of religious teachings. This study provides a basis for developing more effective and accurate instruments to improve the quality of Islamic Religious Education learning at various levels of education.